A systematic review of parenting and feeding practices, children’s feeding behavior and growth stunting in Asian countries - Munawar, Khadeeja; Mukhtar, Firdaus; Roy, Mollika; Majeed, Nida; Jalaludin, Muhammad Yazid (Routledge, 2024)
This systematic review evaluates studies focusing on parenting and feeding practices, children’s feeding behavior, and growth stunting in Asian countries. Eight electronic databases were searched to screen studies published between Jan 2015 and May 2021. There were contradictory findings related to gender differences in growth stunting and factors that reinforce/facilitate or inhibit acquisition of optimum growth in children. Theme of parenting practices showed that time spent on childcare, traditional beliefs about child-care feeding and responsive feeding were also contributing factors. Amidst economic improvement, political, social changes, and worldwide execution of various nutritional programs, stunting continues to be relentlessly persistent and widespread in Asia. Undernutrition disturbs areas of the mind involved in reasoning, reminiscence, locomotor skills and also an adverse influence on the physical and psychological growth of children and ensuing learning capabilities. Stunted children have more anxiety and depression and lower self-esteem than non-stunted children. A public health strategy is required to: (i) properly examine stunting with time through collaborated efforts of community members and various sectors, (ii) tackle malnutrition with steps to enhance maternal nutrition during pregnancy, infant feeding practices and (iii) involvement of effective multi-sectoral partnership programs for management of stunting.